Faktor-Faktor Yang Berpengaruh Terhadap Kejadian Tuberkulosis Pada Wanita di Kabupaten Cilacap Provinsi Jawa Tengah - Nana Sumarna; Ning Rintiswati; Lutfan Lazuardi (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2015)
Background : Tuberculosis (TB) is disease a second major cause of deaths worldwide among infectious diseases, killing nearly 2 million people each year. The variety of problems will arise if the woman was suffering TB especially who are married, pregnant, and have children. Her role as a housewife who had to carry out physical or mental care of children while taking care of her husband will be disturbed. The prevalence of smear positive pulmonary Tuberculosis (TB) in 6 region health center in Cilacap District at 2012, women higher than men.Objective : To know probability of pregnancy, marital status, parity, physical activity, level of education, level of knowledge, the kitchen smoke pollution, history contact with TB patient, residential density, ventilation against TB incidence in women.Method : The type of research was observational analytical case-control design. Sample is 102 people consisting of as many as 51 cases and 51 control. Sampling is done with proportional random sampling techniques. Data were analyzed with the univariabel, bivariabel analysis, and multivariable. Results : Pregnancy (OR 1.2 95% CI 2.4-23.7 p0.04), parity (OR 3.5, 95% CI 1.3-9.7 p 0.01), history of contacts (OR 3.8 95% CI 1.4-10.4 p 0.01) ventilation (OR 2.4 95% CI 7,5-23.7 p 0.00) as a risk factor for the occurrence of TB in women. Conclusion : The incidence of TB in women in Cilacap District a more probable or risk greater in women who were pregnant, high parity, had a history of contacts, and stay at home with the bad ventilation.